2007
DOI: 10.1007/s12011-007-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Calcium and Magnesium in Serum and Hair with Bone Mineral Density in Premenopausal Women

Abstract: Magnesium in serum and hair was associated with BMD in premenopausal women. The ratio of serum calcium to magnesium appears to be a significant indicator of BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…In a previous study, we could observe different [31] whereas dietary Mg reduction-induced bone loss with decreased serum Mg and elevated serum Ca levels in an animal study [32]. These results suggest that Ca and Mg have a cellular antagonism [33] and that balancing Ca and Mg is important to maintain optimal bone density.…”
Section: Discussionmentioning
confidence: 70%
“…In a previous study, we could observe different [31] whereas dietary Mg reduction-induced bone loss with decreased serum Mg and elevated serum Ca levels in an animal study [32]. These results suggest that Ca and Mg have a cellular antagonism [33] and that balancing Ca and Mg is important to maintain optimal bone density.…”
Section: Discussionmentioning
confidence: 70%
“…[30] But another recent research reported hair calcium level is negative associated with BMD and calcium intake. [18] In our study, BMD, calcium intake and hair calcium level have no significant relationship.…”
Section: Discussionmentioning
confidence: 99%
“…A positive relationship between bone mass and dietary magnesium intake was found in young women [123][124][125][126][127], although results are not consistent across all skeletal sites. In postmenopausal women and older men, positive correlations between BMD and magnesium intake have been found although results are not consistent based on gender and race [128][129][130].…”
Section: Magnesiummentioning
confidence: 79%